EFL Teacher’s Strategies in Preparing Classroom Activity for Vocational High School Students - Fauzi Ardiansyah (Journal of English Education Program (JEEP), 2023)
The research reported on teachers’ strategies in preparing classroom activities for vocational high school students. It was obvious that vocational school prepares students to work in particular industries. Thus, the teacher can provide classroom activities that were able to increase the student’s skills. A case study methodology was employed in this research and the data were obtained from classroom observation and non-structured interviews. The topic of this research is an English teacher at a vocational high school. The result found that the teacher prepared the learning materials based on the major that the student had taken and provided the classroom activity that adjusted to the student’s skill program. However, the study also showed that many students still seemed unmotivated and less focused. The teacher explained that it could be the students' less vocabulary mastery that made them hard to pay attention to the learning activity. The findings concluded that (1) the teacher can provide effective classroom activities even though it is still hard to manage the students, and (2) the teacher has provided the classroom activities based on the student’s needs, backgrounds, and skills.